Prevalence of hypertension among females with infertility, and its association with demographics - Azad, Renu; Rathoria, Richa; Chaudhary, Ekta; Rawat, Vishi; Singh, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hypertension (HTN) is a major health problem accelerating worldwide, particularly among reproductive-age females. It may impair fertility through hormonal and vascular mechanisms. This study assesses the prevalence of HTN among females with infertility and its association with demographic and lifestyle factors. Methods: A cross-sectional study was conducted over 12 months in the obstetrics and gynaecology department at Hind institute of medical sciences, Sitapur. A total of 384 infertile females aged 18-49 years were included. A predesigned proforma was used to gather demographic, dietary, and anthropometric data, as well as blood pressure (BP) measurements. The 2017 ACC/AHA guidelines were used to classify HTN. SPSS version 22 was used for the statistical analysis. Results: The mean age of infertile females was 27.87 (6.58) years. The prevalence of HTN among infertile females was 33.1%. Overweight and obesity were present in 40.9% and 20.8% of participants, respectively. HTN was significantly associated with obesity (p<0.0001) and higher socioeconomic status (p=0.016). No significant associations were found with age, religion, family type, livelihood, type of infertility, diet, or junk food intake. Conclusions: A high burden of HTN was observed among infertile women, particularly those with obesity and higher socioeconomic backgrounds. Integration of cardiovascular screening and lifestyle interventions into infertility care is essential.